Pengolahan Limbah Industri Tahu dengan Tanaman Kenaf (Hibiscus cannabinus L.) untuk Menurunkan Kadar Nitrat (Utilization of Kenaf Plant (Hibiscus cannabinus L.) to Reduce Nitrate Levels in Tofu Industrial Wastewater) - Fitria, Firda Lutfiatul (Universitas Tanjungpura, 2024)
Tofu industry waste is rich in nutrients so it can pollute the environment if there is no processing or remediation of soil contaminated by tofu waste. One technology that can be used is phytoremediation, which uses plants to reduce organic and inorganic pollutants in soil, sediment or water. Kenaf plants (Hibiscus cannabinus L.) have the ability to reduce pollutants so they can be used in the phytoremediation process. This research uses bed evapotranspiration with a batch system to measure the reduction in nitrate levels. The variables used in this research were kenaf plant varieties (KR 12 and KR 15), age (30 days and 45 days) and tofu wastewater concentrations of 50% and 75%. The results of pH observations on day 3 ranged from 7.1 - 7.7. Nitrate analysis observations were carried out every 7 days for 28 days. It is known from research results that kenaf 15 plants aged 45 days have the highest removal efficiency.